Establishing and integrating a transoral robotic surgery programme into routine oncological management of head and neck cancer – a UK perspective. Issue 12 (22nd December 2022) - Arora, A; Brunet, A; Oikonomou, G; Tornari, C; Faulkner, J; Jeyarajah, J; Touska, P; Sandison, A; Rovira, A; Simo, R; Jeannon, J-P
Abstract: Background: The introduction of transoral robotic surgery into routine management of patients is complex. It involves organisational, logistical and clinical challenges. This study presents our experience of implementing such a programme and provides a blueprint for other centres willing to establish similar services. Methods: Implementation of the robotic surgery programme focused on several key domains: training, logistics, governance, multidisciplinary team awareness, pre-operative imaging, anaesthesia, post-operative care, finance, patient selection and consent. Programme outcomes were evaluated by assessing operative outcomes of the first 117 procedures performed. Results: The success of the transoral robotic surgery programme has been possible because of the scrupulous planning phase before the first procedure, and the time invested on team awareness and training. Conclusion: Implementation of a new transoral robotic surgery service has led to: the development of a dedicated transoral robotic surgery patient care protocol, the performance of progressively more complex procedures, the inclusion of transoral robotic surgery training and the establishment of several research projects.